Pengaruh Leverage, Struktur Modal, Profitabilitas, Kebijakan Dividen, dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Rizky Amelia; Nursiam Nursiam (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the effect of leverage, capital structure, profitability, dividend policy, and firm size on firm value in manufacturing companies in the industrial sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2020–2023 period. The population used was all manufacturing companies in the industrial sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2020–2023 period. Sampling was conducted using a purposive sampling technique, resulting in 41 companies or 164 data units over four years. After removing 15 outliers, the final sample consisted of 149 data. The data were secondary data from financial reports and company annual reports on the official Indonesia Stock Exchange website (www.idx.co.id) and analyzed using multiple linear regression with SPSS version 26. The results show that: (1) Leverage (DAR) has no effect on firm value; (2) Capital structure (DER) has a positive and significant effect on firm value; (3) Profitability (ROA) has a positive and significant effect on firm value; (4) Dividend policy (DPR) has no effect on firm value; and (5) Firm size has no effect on firm value. Simultaneously, the independent variables significantly influence firm value, with an Adjusted R² value of 20.6%, while the remaining 79.4% is influenced by factors outside the research model.